Pengaruh Kompleksitas Tugas Dan Komunikasi Organisasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Di KPP Pratama Semarang Barat - Budiyono, Budiyono; Kusnilawati, Nunik; Budiati, Yuli (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The concept of this research challenge is how to maximize employee performance with work satisfaction acting as an intervening variable that mediates the influence of task complexity and organizational communication, based on the problem phenomena and research gaps identified. This study examines how task complexity and organizational communication affect worker performance at KPP West Semarang, using job satisfaction as an intervening variable. Using a sampling technique called the census or population research method, 117 respondents made up the study's sample, ensuring that all research samples served as respondents. Hence, 117 KPP Pratama West Semarang personnel served as the study's samples. A questionnaire-based data collection approach and SmartPLS software-based data analysis method are employed. The test findings support Hypothesis 1 by demonstrating that Task Complexity at KPP West Semarang significantly and favorably affects Job Satisfaction. Hypothesis 2 is accepted because organizational communication at KPP West Semarang significantly and favorably affects job satisfaction. At KPP West Semarang, task complexity has a favorable and significant impact on employee performance, indicating the acceptance of Hypothesis 3. At KPP West Semarang, organizational communication significantly improves employee performance, proving the validity of hypothesis 4. At KPP West Semarang, job satisfaction significantly improves employee performance, indicating the acceptance of Hypothesis 5. As an intervening variable, task complexity might enhance employee performance through job satisfaction, indicating the acceptance of Hypothesis 6. Furthermore, it is acknowledged that Hypothesis 7 that Organizational Communication might enhance Employee Performance by using Job Satisfaction as an intervening variable.